Effects of dietary herbal antioxidants supplemented on feedlot growth performance and carcass composition of male goats - Karami, Morteza; Alimon, Abdul Razak; Goh, Yong Meng; Sazili, Awis Qurni; Ivan, Michael (Science Publications, 2010)
Problem statement: In goats production, chevon, meat quality and shelf life are very important, dietary herbs and synthetic antioxidants as dietary supplementation, may be can improve growth performance and carcass characteristics of goats. Approach: Thirty-two male (mean live weight 13.0 kg and 8 months old) were assigned to four dietary treatments, namely, basal diet (control, CN) and basal diet supplemented with Vitamin E (VE), Turmeric powder (TU) or Andrographis paniculata Powder (AP). The diets were fed as total mixed rations ad libitum for a period of 14 weeks. The goats were weighed every month, while feed intake was measured on a weekly basis. Thereafter, the goats were subjected to the Halal slaughter and the carcasses dissected. Result: The daily weight gain was not different (p>0.05) between treatments, but the feed intake was lower (p<0.05) for the AP treatment than for the TU treatment, while the gain: DM intake was lower (p<0.05) for the CN treatment than for the AP treatment. The percentage of total meat in the carcass and the longissimus muscle cut were higher (p<0.05) for the AP treatment than for the CN treatment. Conclusion: It was concluded that dietary antioxidants from natural herbs such as Andrographis paniculata have the potential to improve feed efficiency, increased lean meat and reduced body internal fat in the carcass of goats. Addition of TU increased Average Daily Gain (ADG) and feed intake.